Higher Throughput Methods of Identifying T Cell Epitopes for Studying Outcomes of Altered Antigen Processing and Presentation - Newell, Evan W. (Frontiers in Immunology, 2013)
Variation in the mechanisms that mediate antigen processing, MHC-loading and presentation of peptides allows cells to significantly modulate the repertoire of peptides presented by both MHC Class I or Class II. To more quickly determine how these different modes or modulations of presentation translate into altered immune responses, higher throughput methods for identifying T cell epitopes are needed. Proteomics-based comprehensive cataloging of peptides eluted from MHC is a challenging but ideal way of identifying peptide sequences influenced by variable modes of processing and presentation. Several groups have already been successful with this approach and ongoing technical improvements will broaden its applicability. Subsequently, high content combinatorial peptide-MHC tetramer staining using mass cytometry, as we have recently described, should enable the broad assessment of how these changes are perceived by T cells and translated into an altered immune response. The importance of this analysis is highlighted by evidence that physiologically relevant variation in antigen processing and presentation as well as other factors can give rise to unpredictably different T cell responses.